Ecotourism and public policies: Campos do Jordão (SP) from the perspective of nature - Diniz, Lucas Fernandes; Gomes, Fabiano Garcia; Fedrizzi, Valéria Luiza Pereira (Revista Hipótese, 2021)
Correlating ecotourism and public policies is fundamental for the balanced development of the segment with environmental conservation premises in harmony with local communities combining tourism and nature as factors of local development. This article proposes a research with exploratory and bibliographic procedures, which the case chosen was at the city of Campos do Jordão (SP-Brazil) in the Serra da Mantiqueira. The choice was for convenience and the intense flow of ecotourists and activities in natural areas since the destination has gone through several evolutionary cycles. The results demonstrated how public policies in different governmental spheres interact with ecotourism in locality.
Keywords: Ecotourism; Public Policy; Campos do Jordão